Diagnóstico de las fuentes de financiamiento para las Pymes del cantón Latacunga. - Iza Iza, Marco Antonio (2018)
This researching project is focused on studying the financial sources to which the Pymes go to support their activities and projects. Applying some instruments, it determined that there is a real private financial institutions supporting by their programs and services aimed at small and medium companies (Pymes) area, but do not have an intense as required from the public financial institutions, because there is some kind of difficult to access a credit; so, there is a financial blocking trying to use these institutions. The methodology applied was main quantitative which allowed me to get first-hand information about the sources, object of this study. With the descriptive investigation which uses the survey technique that was applied to the Pymes in Latacunga whose central offices are placed in this canton. The variables lined up in this study could be identified and the perception of small and medium businessmen was confirmed, as well, fronting these intermediate financial organizations both public and private. Furthermore, knowing the financial services scope provided by the local financial institutions to this important sector of the economy in detail. Through this research it could be proved that most of the financial supporting has been given by the private intermediary entities because of the efficiency standards at the moment of bringing the credit. Contradictory to what happens into the public banking which are guided by different administrative policies and systems that block the access to this financial support. Also, this study determined the Pymes internal and external situation related to these financial sources that are very important at the time of getting any kind of resource from these sourcing services. Finally, with this diagnosis it could be concluded the advantages and disadvantages of the current financial sources for the Pymes and establishing the best ways to support their activities, as well. The problem has considered in order to find out new and innovative ways of getting financial support which are defined in the current laws and rules.